(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
The objective of this paper was to prepare and provide resources to pharmacists and other healthcare professionals, enabling them to carry out a critical analysis on drug abuse, acquiring knowledge in several areas that effectively contribute to their personal development in this professional field. Professionals play a crucial role in the reduction and prevention of substances abuse, since they are able to advise patient about illicit drugs, psychotropic medicines and alcohol abuse. There is an urgent need to specialize pharmacists to act in the national public health service and contribute to actions aimed at the surrounding community.